Interpreting the gospel and letters of John: an introduction - Brown, Sherri (William B. Eerdmans Publishing Company, 2017)
Accessible, comprehensive, and up-to-date, Interpreting the Gospel and Letters of John is an ideal text for students new to the discipline of biblical studies. Sherri Brown and Francis J. Moloney present a broad overview of the story of Christianity arising out of its Jewish foundations and proceed to guide readers expertly through the contents of the Gospel and Letters of John. Maintaining that Johannine literature is best understood against the background of the Old Testament covenant metaphor, Brown and Moloney focus on the central role of covenant in the narrative of John's Gospel and highlight the Evangelist's use of fulfillment language. Helpful sidebars, maps, questions for review, and further-reading lists are placed throughout the text, making this volume well suited for classroom use